Status of Adolescent Sexual and Reproductive Health in Nepal - Pitambar Acharya, Gita Rijal (Interdisciplinary Research in Education, 2021)
Adolescence is the transitional stage (10-19 years) of physical and psychological development that occurs during the period from puberty to adulthood. Adolescent and Sexual Reproductive Health (ASRH) is a healthy condition concerning the system, function and reproductive processes owned by a teenager. ASRH had been taken as an important issue after 1994 International Conference on Population and Development (ICPD)which took it as key issue. The main objective of this article is to analyse the general status of ASRH based on the information from Nepal Demographic and health survey 2016 thematically with descriptive design. Marriage, sexual relationship, fertility, knowledge and use of family planning, maternal and child health, knowledge on abortion, physical and sexual violence in terms of ASRH. Besides, policy intervention, gaps and recommendationshave also been discussed briefly.